Social Policies and its Direct Impact on Poverty Reduction - Thapa, Buddhi Bahadur (Himalayan Journal of Sociology and Anthropology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Poverty is one of the major factors that bring obstacles in any kind of growth and development in any part of the world. The problem of poverty is complex in our country so there is a need of appropriate policies that can reduce social inequality and maintain social justice in Nepalese societies. Appropriate social policies can bring positive changes in the life of rural and urban poor. In this light, this article focuses on the role of social policies on poverty reduction and alleviation. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1495 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.46-53